Value First: Comments on Mohan Matthen's 'The Pleasure of Art'. Issue 1 (2nd January 2017) - Gorodeisky, Keren
ABSTRACT: While I welcome Mohan Matthen's insistence that art is connected to aesthetic pleasure, I worry about his commitment to viewing pleasure as prior to, and constitutive of, the value of art. I raise my reservations by (i) dispelling his criticism of the reversed explanatory direction, and (ii) showing problems for his commitment. As an alternative, I offer an account of pleasure that explains it in terms of the independent value of art—an account that is free of the problems Matthen raises against this explanatory approach.